2016
DOI: 10.1109/tit.2016.2517008
|View full text |Cite
|
Sign up to set email alerts
|

The Generalized Lasso With Non-Linear Observations

Abstract: Abstract. We study the problem of signal estimation from non-linear observations when the signal belongs to a low-dimensional set buried in a high-dimensional space. A rough heuristic often used in practice postulates that non-linear observations may be treated as noisy linear observations, and thus the signal may be estimated using the generalized Lasso. This is appealing because of the abundance of efficient, specialized solvers for this program. Just as noise may be diminished by projecting onto the lower d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
196
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 154 publications
(217 citation statements)
references
References 41 publications
20
196
0
Order By: Relevance
“…To our knowledge, this corollary is new. It recovers previous results that only apply to a single, fixed λ, as in [20,11]. It is known to be nearly minimax optimal for many constraint sets of interest and for stochastic noise term z, in which case z 2 would be replaced by its expected value [21].…”
Section: 7supporting
confidence: 78%
See 1 more Smart Citation
“…To our knowledge, this corollary is new. It recovers previous results that only apply to a single, fixed λ, as in [20,11]. It is known to be nearly minimax optimal for many constraint sets of interest and for stochastic noise term z, in which case z 2 would be replaced by its expected value [21].…”
Section: 7supporting
confidence: 78%
“…Predating, but especially following, the works in compressed sensing, there have also been several works which tackle the general case, giving results for arbitrary T [11,25,17,16,1,3,20,21]. The deviation inequalities of this paper allow for a general treatment as well.…”
Section: 6mentioning
confidence: 91%
“…Perhaps surprisingly, Plan and Versyynin [PV16] demonstrated that, even with quantized measurements, the G-Lasso achieves good recovery performance when the measurement vectors are Gaussian 4 . An appealing feature of their theoretical result is that, similar to (2), their error bounds are simple to state and clearly isolate the effect of the specific quantization scheme, on one hand, and of the problem geometry, on the other hand.…”
Section: This Gives Rise To the Following Natural Questionmentioning
confidence: 99%
“…Our works naturally relates to the literature of one-bit compressed sensing (CS) [5]. The vast majority of performance guarantees for one-bit CS are order-wise in nature, e.g., [18], [22], [21], [23]. To the best of our knowledge, the only existing sharp results are presented in [29] for Gaussian measurement vectors.…”
Section: Prior Workmentioning
confidence: 99%